NOTES ON FOOD, GROWTH AND REPRODUCTION OF HOMALOPTERA AMPHISQUAMA TA (WEBER and DE BEAUFORT), (BALlTORIDAE) FROM ALAS RIVER, ACEH, SUMATRA ISLAND - Jacobus W. Mosse; Soetikno Wirjoatmodjo (Treubia, 1999)
pproximately 253 specimens of freshwater fish Homalopteraamphisguamata (Weber and de Beaufort) were collected during dry and rainy seasons from the upper reached of Alas river, Sumatra island in 1981-1983. Their food, growth and reproduction were studied. Phytoplanktonic algae, especially Bacillariophyceae and small aquatic insects are their food preference. The growth pattern was different between sex, that is allometric for the male and isometric for the female.Relatively, there is no difference of condition factor between sex (0.850 for the male and 0.848 for the female). However, tne'vaiues were different between seasons. The mixed value in average was around 0.934 in rainy season and around 0.775 in dry season. Total fecundity highly varied from 63 up to 470 or 93 in average. The bigger size of the fish tended to show higher fecundity value. The percentage number of matured gonads during the rainy season was 8.89-22.55 % and in dry season was 8.21-18.33%. The diameter of matured eggs was around 2.01 mm in average.